Beyond the Grain: Correlating Imaging Findings with Mycetoma Pathogens to Optimize Timely diagnosis and Therapy - Mohammed Fadul; Mustaphaa Bahar; Mohamaed Mustfa; Ahmed Fahal; Amel Omer (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Mycetoma is a devastating, progressively destructive neglected tropical disease highly endemic in Sudan, which holds the highest documented global case count (prevalence of 14.5/100,000). Clinically, it presents as a painless subcutaneous mass with sinuses and grain discharge. Frequent delayed presentation leads to high morbidity, disability, and often necessitates amputation. Advanced cases present a diagnostic challenge as their radiological appearance mimics osteosarcoma and other severe bone diseases. Methods This retrospective cross-sectional study utilized a patient database from the Mycetoma Research Centre (MRC) at Soba University Hospital, Khartoum. The study included 1,109 confirmed mycetoma patients who underwent plain radiography between June 2011 and February 2017. Diagnosis was confirmed by clinical, radiological, cytological/histopathological, and grain culture findings. Radiographs were staged using a standardized mycetoma bone change classification. Data were analyzed using SPSS. Ethical approval was obtained from Sudan Medical Specialization Board and Soba University Hospital. Results The mean age of presentation was 31.1 years, with a high prevalence of eumycetoma (75.7%). Pediatric patients (under 15 years) accounted for 10.6% of the cohort, including the youngest patient at two years old. While Stage 0 was the most common radiological finding (63.4%), nearly one-third of patients (28.6%) presented with advanced disease (Stage III or more). A significant correlation was established between the histopathological/microbiological diagnosis and radiological staging (p=0.001). Eumycetoma was significantly higher in advanced stages (Stage III: 86.4%), consistent with its propensity for causing bone cavities, while actinomycetoma peaked at Stage II. Late presentation was frequent, with a majority of lesions being large (>10 cm). Both lesion size (p=0.01) and occupation (p=0.002) were significantly associated with the radiological stage. Conclusion This study validates a simple radiological staging system for mycetoma, correlating it with disease duration and diagnosis. This maximizes X-ray utility in endemic, low-resource settings, facilitating earlier detection and treatment to prevent disabling progression. MRI remains essential for accurate early-stage extension assessment.